Benefiting from Spontaneously Generated 2D/3D Bulk‐Heterojunctions in Ruddlesden−Popper Perovskite by Incorporation of S‐Bearing Spacer Cation. Issue 14 (17th May 2019) - Yan, Yajie; Yu, Shuang; Honarfar, Alireza; Pullerits, Tõnu; Zheng, Kaibo; Liang, Ziqi
Abstract: 2D Ruddlesden–Popper (RP) perovskite solar cells have manifested superior operation durability yet inferior charge transport compared to their 3D counterparts. Integrating 3D phases with 2D RP perovskites presents a compromise to maintain respective advantages of both components. Here, the spontaneous generation of 3D phases embedded in 2D perovskite matrix is demonstrated at room temperature via introducing S‐bearing thiophene−2−ethylamine (TEA) as both spacer and stabilizer of inorganic lattices. The resulting 2D/3D bulk heterojunction structures are believed to arise from the compression‐induced epitaxial growth of the 3D phase at the grain boundaries of the 2D phase through the Pb−S interaction. The as‐prepared 2D TEA perovskites exhibit longer exciton diffusion length and extended charge carrier lifetime than the paradigm 2D phenylethylamine (PEA)‐based analogues and hence demonstrate an outstanding power conversion efficiency of 7.20% with significantly increased photocurrent. Dual treatments by NH4 Cl and dimethyl sulfoxide are further applied to ameliorate the crystallinity and crystal orientation of 2D perovskites. Consequently, TEA‐based devices exhibit a stabilized efficiency over 11% with negligible hysteresis and display excellent ambient stability without encapsulation by preserving 80% efficiency after 270 h storage in air with 60 ± 5% relative humidity at 25 °C. Abstract : Room‐temperature spontaneously generated 2D/3D bulk‐heterojunctions in 2D Ruddlesden−Popper perovskite solar cells are achieved by introducing thiophene‐2‐ethylamine as both cation spacer and stabilizer, resulting in prolonged exciton diffusion length, extended charge carrier lifetime, and an impressive power conversion efficiency of 7.20%. Dual treatments of NH4 Cl and DMSO further boost the efficiency up to 12% and afford an excellent ambient stability of 270 h without encapsulation.